Technological prospecting: the advancement of goat studies (Research, Society and Development, 2021)
The technological prospection is competitive intelligence processes that allows you to track the information available worldwide and provides it to researchers and/or companies offering panoramas of lines of inquiry that can follow and find new niche markets. Demand care and allied research specifications, instilling the innovation in management methods and processes against the demands of a globalized market, with tough competition, high degree of uncertainty and a large volume of information available. Starting from this assumption, this work had as objective the search for patent applications, patents already granted and utility model showing the word "goats" to quantification, classification and allocation of these requests. This required a search on the website of the INPI (National Institute of Industrial Property) to the knowledge of the records as well as on Google Patents and Espacenet, being found 137 search theme-related files. After that, a selection and classification of this material so that it was possible to observe the specific purposes of these requests and thus achieve an assertive regarding the purpose of the files examined.